The anatomy of grief - Holinger, Dorothy P. (Yale University Press, 2020)
Grief happens to everyone. Universal and enveloping, grief cannot be ignored or denied. This book uses humanistic and physiological approaches to describe grief's impact on the bereaved. Taking examples from literature, music, poetry, paleoarchaeology, personal experience, memoirs, and patient narratives, the author describes what happens in the brain, the heart, and the body of the bereaved. Readers will learn what grief is like after a loved one dies: how language and clarity of thought become elusive, why life feels empty, why grief surges and ebbs so persistently, and why the bereaved cry. Resting on a scientific foundation, this literary book shows the bereaved how to move through the grieving process and how understanding grief in deeper, more multidimensional ways can help quell this sorrow and allow life to be lived again with joy. -- Publisher's description.